Biological Expression of Antigenic Determinants of Murine Leukemia Virus Proteins gp69/71 and p30 - Ikeda, H. (1974)
Antisera to purified structural proteins of Rauscher murine leukemia virus, the major envelope glycoprotein, gp69/71, and the major internal protein, p30, were studied by immunofluorescence of viable and fixed virus-infected cells and by virus neutralization. Group-specific and type-specific determinants of gp69/71 were demonstrated by immunofluorescence and virus neutralization tests, indicating that these determinants are located in the cytoplasm and probably on the cell surface as well as on virus envelope. Antisera against p30 showed anti-group and anti-interspecies activities by immunofluorescence with no virus-neutralizing activity. Both antigenic determinants of gp69/71 were sensitive to guanidine-hydrochloride and to a lesser degree to ether treatment, whereas the group-specific determinants of p30 were relatively stable to these treatments.